(untitled) (Constructionism Conference Proceedings, 2025)
The current paper examines the multimodal and collaborative nature of young children’s educational interactions. The paper draws from a design-based project on 3-5-year-old children’s programming and hones in on the multimodal details of children’s collaborative practices. We investigate video-recorded naturally occurring interactions during small group activities during which children learn programming while playing a storyboard-based game, using two analytical techniques to examine how coding sequences are solved. First, we examine how coding problems are solved within the whole dataset. Following this quantitative analysis of interactional conduct, we use multimodal conversation analysis to examine how collaborative coding unfolds in the intricate details of interaction, including gaze, gestures, and temporal aspects. Findings show how the storyboard fosters both individual scaffolds and collaborative solutions. The multimodal analysis unveils how collaborative coding by children consists of overlapping turns of interaction where children jointly solve sequencing problems using a range of embodied resources. The findings show how constructionism designs can foster collaborative, interactive solutions for young children’s situated coding activities.